(untitled) (Sustainability in Debate, 2024)
The main factors that favour the regeneration of native vegetation in two regions in southeast Brazil were evaluated over an approximate period of 30 years. Region 1 covers 5.2 million hectares and is situated in the northern and northeastern portions of São Paulo. Region 2, located in eastern São Paulo, is formed by the Paraíba do Sul River basin and spans over 1.4 million hectares. In 2016, the area of native forests in Region 1 accounted for 19.3% of the territory against 16.9% in 1988. In Region 2, forests expanded by 83%, from 250,000 to 455,000 hectares. However, while in Region 1, characterised by competition between agricultural crops, the forest gain was modest, in Region 2, marked by steep terrain and a decline in livestock activities, significant natural forest regeneration was favoured. Restoration of native forest vegetation in the state of São Paulo may vary significantly over regions.